Neurokinin-3 Receptor Activation in the Retrochiasmatic Area is Essential for the Full Preovulatory LH Surge in Ewes - Porter, Katrina L. (2014)
Neurokinin B (NKB) is essential for human reproduction and has been shown to stimulate LH secretion in several species, including sheep. Ewes express the neurokinin-3 receptor (NK3R) in the retrochiasmatic area (RCh) and there is one report that placement of senktide, an NK3R agonist, therein stimulates LH secretion that resembles an LH surge in ewes. In this study, we first confirmed that local administration of senktide to the RCh produced a surge-like increase in LH secretion, and then tested the effects of this agonist in two other areas implicated in the control of LH secretion and where NK3R is found in high abundance: the preoptic area (POA) and arcuate nucleus (ARC). Bilateral microimplants containing senktide induced a dramatic surge-like increase in LH when given in the POA similar to that seen with RCh treatment. In contrast, senktide treatment in the ARC resulted in a much smaller, but significant, increase in LH concentrations suggestive of an effect on tonic secretion. The possible role of POA and RCh NK3R activation in the LH surge was next tested by treating ewes with SB222200, an NK3R antagonist, in each area during an E(2)-induced LH surge. SB222200 in the RCh, but not in the POA, reduced LH surge amplitude by about 40% compared to controls, indicating that NK3R activation in the former region is essential for full expression of the preovulatory LH surge. Based on these data, we propose that NKB actions in the RCh are an important component of the preovulatory LH surge in ewes.